PENGARUH BUDAYA SUKU ARFAK (HATAM-MEYAH-MOILE-SOUGB) TERHADAP PERENCANAAN DAN PEMBANGUNAN INFRASTRUKTUR KOTA DI KABUPATEN MANOKWARI - Isir, Happries Januaris; Rante, Harmonis; Rumansara, Enos H. (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2024)
The Papuan community strongly identifies with its culture and customs. What happens in Papua in general, and specifically in Manokwari Regency as the oldest city in Papua/the city where the Gospel entered the Land of Papua, a city rich in history and culture, has not fully actualized its culture into the governance framework established in the regulations of the regency government, the Regional People's Representative Council (DPRD), the Papuan People's Assembly (MRP), the Customary Council (DAP), NGOs, and the Customary Institutions (LMA). Law Number 21 of 2001 granted the Provinces of Papua and West Papua a special status. To this day, the uniqueness and distinctiveness of other regions in Indonesia do not guarantee that planning and development will follow and respect the culture and customs of the indigenous Papuan people, as stipulated in the Special Autonomy Law. Private sectors, state-owned enterprises, the government, and NGOs are rapidly developing their plans, but they do not incorporate the local wisdom of the community. The Papuan people are beginning to erode and neglect their culture, which serves as their symbol and identity. Therefore, the implementation of planning and development rules based on local wisdom, along with the modeling of forms, attributes, carvings, decorations, and ornaments, is a tangible manifestation of cultural preservation.Recognizing that the city of Manokwari's infrastructure development cannot ignore the long-standing values and cultural aspects is crucial. This embodies the aspiration and desire of the Manokwari people to be active participants in their land and culture, not merely spectators.